2011
DOI: 10.1074/jbc.m111.244517
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Zipper EF Hand-containing Transmembrane Protein 1 (Letm1) and Uncoupling Proteins 2 and 3 (UCP2/3) Contribute to Two Distinct Mitochondrial Ca2+ Uptake Pathways

Abstract: Cytosolic Ca2+ signals are transferred into mitochondria over a huge concentration range. In our recent work we described uncoupling proteins 2 and 3 (UCP2/3) to be fundamental for mitochondrial uptake of high Ca2+ domains in mitochondria-ER junctions. On the other hand, the leucine zipper EF hand-containing transmembrane protein 1 (Letm1) was identified as a mitochondrial Ca2+/H+ antiporter that achieved mitochondrial Ca2+ sequestration at small Ca2+ increases. Thus, the contributions of Letm1 and UCP2/3 to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
87
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 53 publications
14
87
1
4
Order By: Relevance
“…Another study has implicated Letm1 in Ca 2ϩ translocation across the IM (14,15). Our results suggest otherwise, agreeing with those that have postulated a role in KHE (1, 3, 10).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another study has implicated Letm1 in Ca 2ϩ translocation across the IM (14,15). Our results suggest otherwise, agreeing with those that have postulated a role in KHE (1, 3, 10).…”
Section: Discussionsupporting
confidence: 82%
“…In all of these model systems, treatment with the chemical K ϩ /H ϩ exchanger nigericin compensates for the loss of Letm1-mediated KHE. However, Letm1 was also identified as a calcium (Ca 2ϩ )/H ϩ antiporter in the genome-wide RNAi screen in Drosophila S2 cells (14), a finding corroborated in a later report (15).…”
supporting
confidence: 67%
“…To test whether RyR1 overexpression can affect ATP production, [ATP] mt was measured using the mitochondrial matrix-targeted FRET-based ATP sensor Ateam by confocal microscopy (see MATERIALS AND METHODS; Fig. 10A) (29,61,79). We confirmed that this ATP sensor was expressed in mitochondria in H9c2 cells after transfection (Fig.…”
Section: Subcellular Localizations Of Overexpressed Ryr1 In Cardiacmentioning
confidence: 62%
“…Mitochondrial Ca 2+ uptake from SOCE in ECs is accomplished by a second type of MCU, which mediates Ca 2+ uptake into mitochondria at nanomolar cytosolic Ca 2+ concentrations and has been termed Letm1 [383] . This is a leucine-zipper-EF hand-containing a TM region which catalyzes the 1:1 electrogenic exchange of Ca 2+ for H + [386] . Conversely, the contribution of the so-called mitochondrial calcium uptake 1 (MICU1), which has recently been discovered by working on HeLa and HEK-293 cells [387] , to endothelial Ca 2+ signaling has not been ascertained yet The mitochondrial NCX (mNCX) is the main mechanism responsible for the outward transport of Ca 2+ towards the cytosol with a stoichiometry of 3Na + :1Ca 2+ (as for the plasmalemmal NCX) [36,41] : the Na + that enters down the electrochemical gradient is exchanged for Ca 2+ [383] .…”
Section: Mitochondrial Camentioning
confidence: 99%